Talkative Felipe Guaman Poma de Ayala and the Linguistic Barriers of Cultural Resistance - Espezúa Salmón, Dorian (2020)
This essay intends to demonstrate when, where, how and why a talkative chronicler expresses himself. I examine the means used by the indigenous author to provide information about the world vision of those who were conquered in their own voices. Nueva corónica y buen gobierno brings to the forefront the dilemma surrounding the language of a ladino Indian who was bilingual and multicultural and used several linguistic and iconic codes to write about an unknown world to the Spanish king. Guaman Poma’swork shows Indian processes of assimilation of Castilian Spanish and Western symbolic systems. Thanks to these processes, Andean informants, translators, scribes or notaries took advantage of alphabetic grafsm to make speak to those who did not have a voice in the colonial accounts. Their goal was to denounce the cultural and ideological conﬂicts in the Andean world.